A comparative synteny analysis tool for target-gene SNP marker discovery: connecting genomics data to breeding in Solanaceae. (3rd June 2018) - Choe, Junkyoung; Kim, Ji-Eun; Lee, Bong-Woo; Lee, Jeong Hee; Nam, Moon; Park, Youn-Il; Jo, Sung-Hwan
Abstract: It is necessary for molecular breeders to overcome the difficulties in applying abundant genomic information to crop breeding. Candidate orthologs would be discovered more efficiently in less-studied crops if the information gained from studies of related crops were used. We developed a comparative analysis tool and web-based genome viewer to identify orthologous genes based synteny as well as sequence similarity between tomato, pepper and potato. The tool has a step-by-step interface with multiple viewing levels to support the easy and accurate exploration of functional orthologs. Furthermore, it provides access to single nucleotide-polymorphism markers from the massive genetic resource pool in order to accelerate the development of molecular markers for candidate orthologs in the Solanaceae. This tool provides a bridge between genome data and breeding by supporting effective marker development, data utilization and communication. Database URL: http://tgsol.seeders.co.kr/scomp/